Intervening Role Use Modern Stevedoring Equipment In Relationship Green Smart Port Implementation And Performance Effectiveness - Asep Suparman; Eny Budi Sri Hayani; Zildan Salman; Daffa Satriawan (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The implementation green and smart port concepts has rapidly developed worldwide, including in Indonesia, although still faces various challenges. This research analyzed the factors influence port performance, with focus on determining role the use modern stevedoring equipment as mediating variable in relationship between implementation green and smart ports and effectiveness of port performance. Research location at Pertamina Port and Logistics Jakarta, which has implemented green and smart ports. Research conducted quantitatively with saturated sample of 102 respondents who all employees handle green and smart ports, using 5 point Likert Scale. Data analyzed using SEM-PLS software and results showed that use of modern stevedoring equipment and implementation of green and smart ports had significant effect with p-value 0.000, 0.006, and 0.008, and increased effectiveness port performance by 97%. This emphasizes the importance of using modern stevedoring equipment and optimal implementation of green and smart ports for enhance effectiveness of port performance.